General Approach for MOF-Derived Porous Spinel AFe2O4 Hollow Structures and Their Superior Lithium Storage Properties - Yu, Hong (2016)
A general and simple approach for large-scale synthesis of porous hollow spinel AFe2O4 nanoarchitectures via metal organic framework self-sacrificial template strategy is proposed. By employing this method, we can successfully synthesize uniform NiFe2O4, ZnFe2O4, and CoFe2O4 hollow architectures that are hierarchically assembled by nanoparticles. When these hollow microcubes were tested as anode for lithium ion batteries, good rate capability and long-term cycling stability can be achieved. For example, high specific capacities of 636, 449, and 380 mA h g–1 were depicted by NiFe2O4, ZnFe2O4, and CoFe2O4, respectively, at a high current density of 8.0 A g–1. NiFe2O4 exhibits high specific capacities of 841 and 447 mA h g–1 during the 100th cycle when it was tested at current densities of 1.0 and 5.0 A g–1, respectively. Discharge capacities of 390 and 290 mA h g–1 were delivered by the ZnFe2O4 and CoFe2O4, respectively, during the 100th cycle at 5.0 A g–1.